Peningkatan Pemahaman Siswa Dalam Mendorong Partisipasi Pemilih Pemula Guna Menciptakan Masyarakat Sadar Politik - Lira, Muhammad Adnan (ADPERTISI, 2024)
General elections (Pemilu) in Indonesia serve as a cornerstone of democracy, allowing citizens to voice their political aspirations. The electoral process involves the organization by institutions such as the General Election Commission and the Election Supervisory Body. Political participation, particularly from young voters, plays a crucial role in ensuring the success of democracy. Community service at SMA Muhammadiyah Limbung, Gowa Regency, is aimed at enhancing the understanding of young voters regarding political participation, especially leading up to the 2024 elections. Utilizing the Pre-Post Test Design method with questionnaires as data collection instruments, the activity includes pre-tests, workshops, and post-tests to evaluate the effectiveness of community service. Evaluation results show an improvement in students' understanding from the